PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN DI INDONESIA TAHUN 2009-2012 - B01108123, ERICK SIDHARTA (Jurnal Pembangunan dan Pemerataan, 2014)
The research entitled The Influence of Inflation and Economic Growthto Unemployment Rate In Indonesia Year 2009-2012. This purpose of this research is to determine whether there is influence of Inflation and Economic GrowthtoUnemployment RateIn Indonesia Year 2009-2012. To prove the hypothesis of the research with multiple linier regression analyzes used SPSS. Simultaneous regression calculation results showed that there was no significant relationship between the independent variable (Inflation and Economic Growth), to dependent variable(Unemployment Rate),while the partial regression calculation results showed that the only variable inflation significant negative effect on the unemployment rate, which means any increase in inflation will be followed by a decrease in unemployment. Value of coefficient of determination ( R2 ) of 0.146 or 14.6 % which indicates that the percentage of donations influence the ability of the independent variables ( Inflation and Economic Growth ) on the dependent variable ( unemployment ) , while the rest is influenced by the other independent variables were not examined . Keywords :Inflation, Economic Growthand Unemployment